Bullous leukemia cutis mimicking facial cellulitis - Luciana de Sales Caldato; Juliana de Sousa Britto; Ligia Niero-Melo; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2016)
Abstract Bullous leukemia cutis is an uncommon clinical manifestation of cutaneous infiltration by leukemic cells, from B-cell chronic lymphocytic leukemia. We present the case of a 67-year-old, female, chronic lymphocytic leukemia patient. She was taking chlorambucil and developed facial edema with erythema and warmth, misjudged as facial cellulitis. Two days later, she developed bullous lesions in the arms, legs, neck and face. The histopathology of facial and bullous lesions confirmed leukemia cutis. All lesions disappeared following the administration of rituximab combined with cycles of fludarabine and cyclophosphamide. Although soft tissue infections are common complications in patients undergoing chemotherapy, leukemia cutis can also resemble cellulitis.